Forum Komunikasi dan Koordinasi Sekolah Program Kampus Mengajar Angkatan III di SDN Murung Raya 3 Banjarmasin - Iin Ariyanti (LPMP Imperium, 2022)
Kampus Mengajar is part of the Merdeka Belajar-Kampus Merdeka (MBKM) program, which aims to provide opportunities for students to learn and develop themselves through activities outside lecture class. One of the targeted schools for placement of MBKM Batch 3 is at SD Negeri Murung Raya 3 Banjarmasin. A mandatory forum for students in MBKM 3 must initiate a communication and coordination forum with schools. The Communication and Coordination Forum activity with the SDN Murung Raya 3 school was held offline on April 11, 2022, at SDN Murung Raya 3 Banjarmasin. This activity was attended by school principals, teachers, students of MBKM, and Field Supervisors. The agenda was discussed at the school communication and coordination forum, namely the results of school observations, program activities carried out during March, and planned program activities for Ramadan Month and After. The results obtained from discussions during the communication and coordination forum were competitions in the month of Ramadhan, teaching/collaborating with teachers in the learning process, sharing of IT (technology adaptation) with the teachers of SDN Murung Raya 3 Banjarmasin, and social service.